A defense of the moral and legal right to secede. Issue 1 (2nd January 2021) - Vaca, Moises; Artiga, Marc
ABSTRACT: We defend the moral and legal right to secede in accordance with plebiscitary theory. Our paper has three main goals. First, by offering a schematic characterization of plebiscitary theory, the main arguments in its favour (and the main objections to them), we contribute to clarify the structure of this complex debate. Second, we stress the point that, if the moral right to secede is established, the resistance for its inclusion into positive law is unjustified. Finally, by addressing old and new objections to plebiscitary theory, we hope to make a compelling case for a wider recognition of secessionist rights.